Key Concepts and Principles of Futurosynergetics - Bozarov Dilmurod Mirzarasulovich (Scientific Trends, 2025)
This academic article explores the concept of futurosynergetics as a result of epistemological integration between futurology and synergetics within a socio-philosophical framework. It argues that under the conditions of global transformation, futurosynergetics serves as a crucial theoretical foundation for designing future-oriented strategies. The article highlights the significance of historical holism, the dynamics of open systems, meta-historical reasoning, and axiological perspectives in constructing images of the future. Futurosynergetics is interpreted as a conceptual space that synthesizes scientific, cultural, and ethical dimensions of humanity's future vision.
Keywords: Futuro synergetics, futurology, synergetics, historical holism, meta-history, forecasting, axiology, future imagery.